EFFECT OF TIME AND SUJI LEAF (Pleomele Angustifolia) ADITIVE CONCENTRATION ON THE CHARACTERISTIC OF CASSAVA BASED RICE ENRICHED WITH TUNA PROTEIN - Nurlina, Nurlina (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Food that has specially scent is more preferred by consumers. Analog rice that enriched with tuna flour have a stench smell. Oneof themethodwas to relieve the stench smell is by soaking to suji leaf extract. The purpose of this study is characteristic test of analog ricemade fromcassava flour enrichedwith protein of tuna, and investigating the effect of time and concentration of additives suji leaf with the physical and chemical properties of rice analog. Several parameters was evaluated such us protein content, moisture content, color, bulk density, uniformity of grain and organoleptic tests. This study used completely randomized factorial design. The first factor is time of soaking (5,10, and 15 minute) and the second factor is concentration of suji leaf extract (20, 40,60, and 80%). The ratio of cassava flour and protein of tuna in the research is 92,5%: 7,5%. The result showed that protein contain of analog rice is 4,4687%. Moisture content of analog rice is between 10,48 – 12,61%. The longer of soaking time and high concentration canincreasedmoisture content of analog rice.Dominant colour analog rice is brown. Uniformity highest of granules produced on the size 1.7 – 3.33mesh. Treatment received by the panel based ontest organoleptik by scent is treatment of analog rice that soakedwith 15minutes and ratioleaf suji 400: 1000 g/ml. Keyword : Suji leaf, Scent, Rice analog, Protein.